The genomic landscape of core-binding factor acute myeloid leukemias - Faber, Zachary J; Chen, Xiang; Gedman, Amanda Larson; Boggs, Kristy; Cheng, Jinjun; Ma, Jing; Radtke, Ina; Chao, Jyh-Rong; Walsh, Michael P; Song, Guangchun; Andersson, Anna K; Dang, Jinjun; et al. (Nature genetics, 2016)
Lars Bullinger, Jinghui Zhang, Jeffery Klco, James Downing and colleagues report a detailed genomic analysis of pediatric and adult core-binding factor acute myeloid leukemias (CBF-AMLs). They identify recurrent mutations in CCND2 , MGA , DHX15 and ZBTB7A and highlight dramatic differences in the landscape of cooperating mutations between different CBF-AML subtypes. Acute myeloid leukemia (AML) comprises a heterogeneous group of leukemias frequently defined by recurrent cytogenetic abnormalities, including rearrangements involving the core-binding factor (CBF) transcriptional complex. To better understand the genomic landscape of CBF-AMLs, we analyzed both pediatric ( n = 87) and adult ( n = 78) samples, including cases with RUNX1 - RUNX1T1 ( n = 85) or CBFB - MYH11 ( n = 80) rearrangements, by whole-genome or whole-exome sequencing. In addition to known mutations in the Ras pathway, we identified recurrent stabilizing mutations in CCND2 , suggesting a previously unappreciated cooperating pathway in CBF-AML. Outside of signaling alterations, RUNX1 - RUNX1T1 and CBFB - MYH11 AMLs demonstrated remarkably different spectra of cooperating mutations, as RUNX1 - RUNX1T1 cases harbored recurrent mutations in DHX15 and ZBTB7A , as well as an enrichment of mutations in epigenetic regulators, including ASXL2 and the cohesin complex. This detailed analysis provides insights into the pathogenesis and development of CBF-AML, while highlighting dramatic differences in the landscapes of cooperating mutations for these related AML subtypes.